2020
DOI: 10.1111/ecin.12930
|View full text |Cite|
|
Sign up to set email alerts
|

Benign Neglect of Covenant Violations: Blissful Banking or Ignorant Monitoring?

Abstract: Theoretically, bank's loan monitoring activity hinges critically on its capitalization. To proxy for monitoring intensity, we use changes in borrowers' investment following loan covenant violations, when creditors can intervene in the governance of the firm. Exploiting granular bank-firm relationships observed in the syndicated loan market, we document substantial heterogeneity in monitoring across banks and through time. Better capitalized banks are more lenient monitors that intervene less with covenant viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
(149 reference statements)
1
2
0
Order By: Relevance
“…The result ofAshcraft (2008) is in line with the theoretical literature showing that debt covenants can reduce default risk ex-ante by better aligning the interests of shareholders and managers with those of bondholders and by prohibiting actions that might increase the likelihood of distress(Colonnello et al, 2021;Holmström & Myerson, 1983;Smith & Warner, 1979). 3 Banks have to meet regulatory requirements in terms of capital.…”
supporting
confidence: 83%
“…The result ofAshcraft (2008) is in line with the theoretical literature showing that debt covenants can reduce default risk ex-ante by better aligning the interests of shareholders and managers with those of bondholders and by prohibiting actions that might increase the likelihood of distress(Colonnello et al, 2021;Holmström & Myerson, 1983;Smith & Warner, 1979). 3 Banks have to meet regulatory requirements in terms of capital.…”
supporting
confidence: 83%
“…Greenwald et al (2020) showed that firms rely on credit lines more than other types of credit after a fall in cash flow. However, if the bank or the firm show financial deterioration, the agreement can be jeopardised (Acharya et al, 2020;Colonnello et al, 2021).…”
Section: Ijebr 306mentioning
confidence: 99%
“…However, if the bank or the firm show financial deterioration, the agreement can be jeopardised (Acharya et al. , 2020; Colonnello et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%